Optimasi Keuntungan Produksi Gorong-Gorong Menggunakan Metode Simpleks pada Usaha Konblock Bangun Lestari - Fauzi Nurhamdi; Syarif Hidayat; Pradita Eko Prasetyo Utomo; Oki Dahwanu (KERNEL: Jurnal Riset Inovasi Bidang Informatika dan Pendidikan Informatika, 2026)
This study aims to optimize the production profit of concrete culvert products at Konblock Bangun Lestari using the simplex method. The observed business produces three types of culverts with different dimensions, material requirements, and processing times. Data were collected through direct field observation and interviews to obtain information on resource availability, including cement, sand, and working hours. A linear programming model was formulated with the objective of maximizing profit under material and time constraints. The simplex method was applied to determine the optimal production combination. The results show that producing 30 units of type B culverts yields the maximum profit of Rp12,300,000 while fully utilizing available resources. This finding demonstrates that the simplex method can effectively support production decision-making in small-scale manufacturing businesses.